Experimental study on impulse discharge machinability of concave micro-array using a micro-tip array electrode. Issue 6 (2nd November 2018) - He, Quanpeng; Xie, Jin; Guo, Ruibin; Ma, Peixin; Lu, Yanjun
GRAPHICAL ABSTRACT: ABSTRACT: It is difficult for mechanical machining to fabricate concave micro-array due to size limit and micro-tool wear. Hence, electro discharge micro-machining is proposed to fabricate concave micro-array using micro-tip array electrode. The objective is to explore the batch micro-machinability of various metallic materials such as die steel, titanium alloy and cemented carbide. First, micro-grinding with diamond wheel micro-tip was performed to fabricate pyramid micro-tip array on electrode surface; then, impulse discharge removal derived from the electrode tips was employed to gradually machine the concave micro-array on metallic surfaces; finally, micro-machined shape and corresponding machining performances were investigated. It is shown that the micro-machining performances depend on material melting point, electric conductivity, and thermal conductivity. Low melting point and electric conductivity lead to good micro-machined shape with small relative wear rate. High electric conductivity and low melting point produce small surface roughness, large micro-removal rate and discharge energy efficiency. Low thermal conductivity leads to large aspect ratio and micro-removal rate. It is confirmed that die steel produces small surface roughness, large micro-removal rate and discharge energy efficiency, whereas titanium alloy produces large aspect ratio and small relative wear rate.